E-cigarette user compliance with COVID-19 health protocols in Yogyakarta - Khuzaimah, Eriyani; Padmawati, Retna Siwi; Bintoro, Bagas Suryo (BKM Public Health and Community Medicine, 2022)
Purpose: This study aims to explore the compliance of e-cigarette users during the COVID-19 pandemic. Method: This research is qualitative research with a phenomenological approach. Data were collected using in-depth interviews, semi-structured guidelines, and observation. The informants were selected using a snowball sampling approach, with a total of 10 e-cigarette users, two health promotion officers, and two e-cigarette shop employees. The validity of research data using triangulation and member checking. Results: The informants still need to fully comply with the policy on using e-cigarettes during the COVID-19 pandemic because the informants still lend each other e-cigarette devices and do not comply with health protocols when using e-cigarettes outdoors. Although this habit is still practiced, the informants are aware that this habit is risky, especially during a pandemic. The use of e-cigarettes during a pandemic can relieve boredom, boredom, and stress. Informants feel that there are different situations, such as community activities that are not running, and the income of e-cigarette sellers is decreasing. The way to access e-cigarettes is different from before the COVID-19 pandemic. Conclusion: E-cigarettes during the COVID-19 pandemic are dangerous, especially the habit of sharing e-cigarettes and gathering without establishing health protocols. However, e-cigarette users tend to ignore and stick to the habit.